1983
DOI: 10.1161/01.res.52.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by carotid baroreflex of exercise-induced increases in arterial pressure.

Abstract: SUMMARY. Mean arterial blood pressure, heart rate, and cardiac output were measured during continuous graded exercise (5.5 km/hr; 0, 7, 14, and 21% grades) in conscious dogs, under each of the following four conditions: (1) baroreceptors intact, (2) chronic aortic arch denervation, (3) chronic aortic arch denervation and surgical preparation of the carotid sinuses for later reversible vascular isolation, and (4) chronic aortic arch denervation and carotid sinuses vascularly isolated at a fixed pressure. Arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
75
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 34 publications
9
75
0
1
Order By: Relevance
“…It is generally accepted that the baroreflex is reset to a higher pressure during exercise with little change in sensitivity, and this allows the arterial pressure to increase with exercise (5,17,26,28). Several investigators have shown that arterial baroreceptors act as an inhibitory signal during exercise to oppose sympathoexcitation (25,37,38). Sheriff et al (32) examined the extent to which arterial baroreflexes attenuate the increase in the pressor response evoked by the muscle metaboreflex during mild exercise in conscious dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that the baroreflex is reset to a higher pressure during exercise with little change in sensitivity, and this allows the arterial pressure to increase with exercise (5,17,26,28). Several investigators have shown that arterial baroreceptors act as an inhibitory signal during exercise to oppose sympathoexcitation (25,37,38). Sheriff et al (32) examined the extent to which arterial baroreflexes attenuate the increase in the pressor response evoked by the muscle metaboreflex during mild exercise in conscious dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators showed that the pressor reflexes to static muscle contraction in anesthetized animals as well as metaboreflex activation during mild exercise in conscious animals were greater after denervation of the arterial baroreceptors and concluded that arterial baroreflexes attenuate the pressor response initiated by activation of skeletal muscle afferents (32, 37). Together, these findings suggest that afferent input of the arterial baroreceptors acts as an inhibitory signal during dynamic exercise to oppose sympathoexcitation induced by activation of skeletal muscle afferents (25,26,32,38). However, the extent to which the arterial baroreflex modifies the mechanisms mediating muscle metaboreflex pressor responses is unknown.…”
mentioning
confidence: 95%
“…Evidence for a central mechanism, considered to be a release of inhibitory commands from the motor cortex to the parasympathetic center, 16 or afferent stimulation from baroreflex or chemoreflex functions, 17 has typically utilized the initial R-R interval changes during the post-exercise recovery periods. Imai et al demonstrated that a release of inhibitory central command rather than baro-or chemoreceptor stimulation may play an important role in postexercise vagal reactivation, because the HR during the first 30 s of recovery minimally depends on the exercise intensity.…”
Section: Discussionmentioning
confidence: 99%
“…49 This latter point remains controversial; arterial baroreceptor reflexes of conscious dogs appear to continue to operate effectively during treadmill exercise. 50 " 52 The strong association we observed between BRS and blood pressure variability could be explained if the reflex regulation of blood pressure was preserved during physical activity but was less potent in hypertensive than in normal subjects.…”
mentioning
confidence: 90%